A comprehensive theoretical investigation on the thiophene hydrodesulphurisation mechanism over sulphided Co–Mo catalysts supported by ZSM-5, FAU, Beta and MCM-22 zeolites. Issue 1 (2nd January 2023) - Yin, Jiabin; Xia, Deping; Sun, Huai; Li, Suyang; Sun, Yingxin; Han, Sheng; Li, Qianggen
ABSTRACT: We have theoretically studied the hydrodesulphurisation (HDS) mechanism of thiophene and its hydrogenated derivatives over sulphided Co–Mo catalysts supported by four zeolites (ZSM-5, FAU, Beta, MCM-22) by a two-layer ONIOM (our Own N-layered Integrated molecular Orbital and molecular Mechanics) method. Due to low energy barriers, the thiophene can be hydrogenated to 2, 3-dihydrothiophene (2, 3-DHT), 2, 5-dihydrothiophene (2, 5-DHT) and tetrahydrothiophene (THT). Direct desulphurisation (DDS) and hydrogenolysis desulphurisation (HYD) pathways were investigated in detail. The calculated results show that in DDS mechanism of thiophene, the rate-determining step is the C–S bond cleavage. In HYD mechanisms of 2, 5-DHT, 2, 3-DHT and THT, the rate-determining step is hydrogen transfer on ZSM-5, FAU and Beta zeolites except MCM-22 zeolite. The HYD of 2, 3-DHT and THT should occur by the stepwise pathway. But for the 2, 5-DHT, the concerted pathway is probably more favourable than the stepwise pathway. The reduced density gradient (RDG), differential charge density (DCD), and local orbital locator (LOL) maps show that for all transition states (TSs), there are complicated van der Waals (VDW) and electrostatic interactions between the organic fragment and the catalytic centre.